The pregnancy experience of Korean mothers with a prenatal fetal diagnosis of congenital heart disease - Yu-Mi Im; Tae-Jin Yun; Il-Young Yoo; Sanghee Kim; Juhye Jin; Sue Kim (BMC, 2018)
Abstract Background Prenatal diagnosis of fetal congenital heart disease (CHD) is becoming widely available but there is a lack of understanding on such expectant mothers' experiences during pregnancy. This was the first study to investigate the pregnancy experience of Korean mothers with a prenatal fetal diagnosis of CHD. Methods In-depth interviews were conducted with 12 mothers regarding their child's prenatal diagnosis of CHD and the adaptive processes during pregnancy. The data were transcribed and analyzed according to the grounded theory framework. Results When the diagnosis of fetal CHD was suspected, mothers desperately sought accurate information regarding CHD while hoping in vain for a misdiagnosis. When the definitive diagnosis was made, most pregnant women experienced psychological trauma and pain, framed in the stigma and burden of having an imperfect child. Provision of accurate health advice and emotional support by a multidisciplinary counseling team was crucial at this phase, forming recognition that CHD could be treated. When fetal movements were felt, mothers came to acknowledge the fetus as an independent being, and made their best efforts to protect the fetus from harmful external influences using traditional TaeKyo mindset and practices, which in turn, were helpful in restructuring the meaning of the pregnancy. Conclusions Mothers went through a dynamic process of adapting to the unexpected diagnosis of CHD, which was closely linked to being able to believe that their child could be treated. Early counseling with precise information on CHD, continuous provision of clear explanations on prognosis, sufficient emotional support, and well-designed prenatal education programs are the keys to an optimal outcome.